Annotated history - the implications of reading Psalm 34 in conjunction with 1 Samuel 21-26 and vice versa - Botha, Phil J. (Old Testament essays, 2008)
In a late phase of redaction, some of the psalms in the first and second Davidic Psalter were supplied with headings that contain biographical references to David. One of these psalms is Psalm 34. The shared traits between Psalm 34 and the account of David's flight from Saul are investigated in detail. It is shown that 1 Samuel 24-26 should be included in the comparison. The editorial effect of the link between David's life and Psalm 34 on the understanding of Psalm 34 is discussed, as well as the influence of reading Psalm 34 in conjunction with this part of David's history. The conclusion is reached that Psalm 34 does not only serve to present David as an example and object of identification for those who read the Psalms, but that he in the first place lends authority to the exhortations directed at believers to stay true to the code of conduct of the poor pious people. Because of this connection, the image of David is enhanced, so that he takes on the roles of wisdom teacher, theologian, suffering servant, and inspired author as well.